KEARIFAN LOKAL BAKAR LAHAN DI KALIMANTAN SELATAN HARMONISASI HUKUM ISLAM DAN HUKUM NASIONAL - Rahmadi Hasbullah (An-Nahdhah | Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2024)
This study examines the dispensation for land clearing by burning based on local wisdom for the people of South Kalimantan in the perspectives of Islamic law and national law. Land clearing by burning is one of the traditional methods still practiced by indigenous communities in South Kalimantan, although this practice has negative environmental impacts. This research aims to understand how national law in Indonesia regulates land clearing by burning on a limited scale, as well as how Islamic law views this practice in the context of local wisdom. Furthermore, the study seeks to find solutions for harmonizing national law and Islamic law in regulating land clearing by burning. The results show that national law provides room for this practice on a limited scale with strict provisions to prevent environmental damage. Islamic law, on the other hand, acknowledges the importance of local wisdom as long as it does not harm the environment and emphasizes the principles of maslahah mursalah (public benefit) and hifz al-bi’ah (environmental preservation). Therefore, harmonization between national law and Islamic law can be achieved by involving indigenous communities, the government, and religious leaders in overseeing and implementing clearer and more effective regulations.